Standards in Genomic Sciences - Garrity, George
Standards in Genomic Sciences is an open-access journal for rapid dissemination of concise genome and metagenome reports, detailed standard operating procedures, meeting reports, reviews and commentaries, data policies, white papers and other gray literature that is relevant but currently absent from the scholarly literature.